The Effect of Entrepreneurship And Leadership On The Performance Of Chinese Smes: The Role Of Organisational Culture As A Mediating Factor - Luo Xiaoli; Dhakir Abbas Ali (Revista Electronica de Veterinaria, 2024)
The purpose of this research is to conduct an empirical inquiry of the link between the performance of small and medium-sized businesses (SMEs) and entrepreneurial leadership, entrepreneurial strategy, and technological innovation skills. We investigate the possibility of intrinsic organisational traits acting as possible mediators between entrepreneurial leadership and the performance of small and medium-sized businesses (SMEs). These intrinsic organisational characteristics include entrepreneurial orientation, team creativity, dynamic skills, and competitive advantage. The dependable PLS-SEM approach was used to the data of 182 small and medium information technology enterprises in Quang Trung Software City, which is located in Ho Chi Minh City, Vietnam. The empirical results suggest that small and medium-sized enterprises (SMEs) may benefit from entrepreneurial leadership via the whole spectrum of creative and dynamic team abilities as well as competitive advantages. The ability to innovate with technology may be beneficial to small and medium-sized businesses (SMEs), but an entrepreneurial attitude is not beneficial to these businesses. In addition, an entrepreneurial attitude does not have a moderating influence on the relationship between entrepreneurial leadership and the achievement of success by SMEs. Last but not least, based on these results, we are in a position to reach pertinent conclusions and provide helpful advice for enhancing the management of entrepreneurial inspiration and promoting its cultivation.